Nanog, in Cooperation with AP1, Increases the Expression of E6/E7 Oncogenes from HPV Types 16/18 - Yakelin Díaz-Tejeda; Miriam C. Guido-Jiménez; Helga López-Carbajal; Alfredo Amador-Molina; Rocío Méndez-Martínez; Patricio Gariglio-Vidal; Marcela Lizano; Alejandro García-Carrancá (Viruses, 2021)
Persistent infections with some types of human papillomavirus (HPV) constitute the major etiological factor for cervical cancer development. Nanog, a stem cell transcription factor has been shown to increase during cancer progression. We wanted to determine whether Nanog could modulate transcription of E6 and E7 oncogenes. We used luciferase reporters under the regulation of the long control region (LCR) of HPV types 16 and 18 (HPV16/18) and performed RT-qPCR. We found that Nanog increases activity of both viral regulatory regions and elevates endogenous E6/E7 mRNA levels in cervical cancer-derived cells. We demonstrated by in vitro mutagenesis that changes at Nanog-binding sites found in the HPV18 LCR significantly inhibit transcriptional activation. Chromatin immunoprecipitation (ChIP) assays showed that Nanog binds in vivo to the HPV18 LCR, and its overexpression increases its binding as well as that of c-Jun. Surprisingly, we observed that mutation of AP1-binding sites also affect Nanog’s ability to activate transcription, suggesting cooperation between the two factors. We searched for putative Nanog-binding sites in the LCR of several HPVs and surprisingly found them only in those types associated with cancer development. Our study shows, for the first time, a role for Nanog in the regulation of E6/E7 transcription of HPV16/18.